The development of Hemodialysis Units in the Army Hospital - Rudy Dwi Laksono; Titih Huriah; Arlina Dewi (Publisher Cv. Inara, 2021)
Patients with renal disease require special care.This study aims to develop a hemodialysis unit in the Army Hospital that require the act of washing the blood as a form to improve health services for patients with kidney failure. In this study, the majority of patients covered by the National Health insurance. Research methods namely method a case study with quantitative descriptive analysis.The results of this study show that the development of the hemodialysis unit will give a positive impact for the patient and for the hospital. The review will be the addition of hemodialysis machines, the addition of a new building, the addition of shift nurse can be seen that all these options will be profitable in the foreseeable future. This of course can make the best judgment for the Hospital in determining a decision for the sake of improving health care for the patient.